MÉTODOS PARA A DETERMINAÇÃO DA PRESENÇA DE Azotobacter chroococcum NO SOLO - Galli, Ferdinando (REVISTA DE AGRICULTURA, 2016)
MÉTODOS PARA A DETERMINAÇÃO DA PRESENÇA DE Azotobacter chroococcum NO SOLO